Perbedaan Fungsi-Fungsi Public Relations dalam Sosialisasi Pemilihan Kepala Daerah (Pilkada) Ã¢â‚¬Å“Kasus di KPUD Yogyakarta dan KPUD BantulÃ¢â‚¬Â - Purwandari, Emma Octavia (Jurnal ILMU KOMUNIKASI, 2009)
Abstract: This research attempts to analyze the differences of Public Relations (PR) function in local election (Pilkada). Pilkada is a democratic process in Indonesia. Government needs big participation of society, as one successful point of pilkada is participation of society. Effort to bring public politics participation cannot be separate from politics socialization process. Socialization process is public attitude establishment and politics orientation process. Pilkada socialization carried out by KPUD (Komisi Pemilihan Umum Daerah) as executor. To make an effective socialization to public, KPUD needs to use specific function called Public Relation. Communication activity between organization and its public divided into some part of PR function, including publicity, advertising, press agentry, lobbying, issue management, investor relation and public affair. Basically, implementation of PR function in the process of PILKADA may be different in each region. It becomes the reason why author want to compare KPUD Yogyakarta and Bantul. Governance system differences among both regions would affect in government’s socialization policy. Those differences depend on population, social classes, demographic condition and personal motivation. It is also effecting in PR function held by government, as in media and in society as target operation